Human retinal pigment epithelium (RPE) transplantation: outcome after autologous RPE-choroid sheet and RPE cell-suspension in a randomised clinical study. Issue 3 (7th July 2010) - Falkner-Radler, Christiane I; Krebs, Ilse; Glittenberg, Carl; Považay, Boris; Drexler, Wolfgang; Graf, Alexandra; Binder, Susanne
Abstract : Aims: To evaluate the outcome after two types of retinal pigment epithelium (RPE) transplantation techniques. Methods: Fourteen consecutive patients with advanced exudative age-related macular degeneration (AMD) were randomly assigned to RPE-choroid sheet transplantation (group 1) or RPE cell-suspension transplantation (group 2). Outcome measures included best corrected distance and near visual acuity (BCVA), complication and recurrence rates, autofluorescence (AF), angiography, and time-domain and spectral-domain optical coherence tomography (TD- and SD-OCT). Results: A gain of three or more lines in BCVA at 24 months was found in two patients in group 1 and in one patient in group 2, whereas a loss of vision of three or more lines occurred in one patient in each group. Revision surgery for proliferative vitreoretinopathy was required in one patient in group 1. Epiretinal membranes developed in two patients in group 1 and in one patient in group 2. No recurrence occurred in this series. AF showed hyperfluorescence coincident with the graft in group 1, and hyper- and hypofluorescence in irregular patterns in group 2. Revascularisation of the graft was present in all patients in group 1, and a normal choroidal vasculature in the area of RPE atrophy in all patients in group 2. OCT showed a decrease in retinal thickness in all patients, with an improved visualisation of inter- and intralaminar structures with SD-OCT. Conclusion: The anatomical and functional outcome after both RPE transplantation techniques was comparable. Intrastructural irregularities of the sheet assessed using SD-OCT might explain the rather limited visual gain in otherwise successful sheet transplants. Clinical Trial Registration: NCT00401713